2019
DOI: 10.1186/s12970-019-0308-5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between vitamin D status and depression in a tactical athlete population

Abstract: Background Stressors inherent to the military, such as combat exposure, separation from family, and strenuous training, collectively contribute to compromised psychological resilience and greatly impact military performance. Methods This retrospective review of records was conducted to determine whether vitamin D status was associated with diagnoses of depression and if diagnoses differed by geographic location. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
1
6
0
2
Order By: Relevance
“…They nally found signi cant relationship among participant with vitamin D de ciency and depression. But the number of male (n = 9799) is more than the female(1121) (30). Similarly, John C. Umhau reported the signi cant correlation between suicide and vitamin D de ciency in 2013 among active duty military.…”
Section: Discussionmentioning
confidence: 98%
“…They nally found signi cant relationship among participant with vitamin D de ciency and depression. But the number of male (n = 9799) is more than the female(1121) (30). Similarly, John C. Umhau reported the signi cant correlation between suicide and vitamin D de ciency in 2013 among active duty military.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast with our finding, Schaad et al , in 18–67 years old males and females, found a significant relationship between vitamin D deficiency and depression. However, the number of males ( n 9799) was notably more than the number of female counterparts ( n 1121), which likely biased the findings ( 54 ) . Similarly, Umhau reported a significant correlation between suicide and vitamin D deficiency among active-duty military personnel, where the number of males ( n 467) was significantly greater than the number of females ( n 19) ( 26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…However, research reports on this topic in various regions are still insufficient; therefore, based on the results of this study in Korea, additional studies in various regions and further studies on multinational backgrounds will be needed in the future. A recent study by Schaad et al showed that there was more vitamin D deficiency at higher latitudes than at lower latitudes, and that the prevalence of depression was related to vitamin D deficiency [ 29 ]. Because vitamin D synthesis and metabolism associated with depression are influenced by various factors, such as sociodemographic, geographic, genetic, and ethnic factors [ 30 , 31 , 32 ], a study to investigate the relationship between vitamin D and depression in terms of geographic differences would be complicated.…”
Section: Discussionmentioning
confidence: 99%